Scoping Review: Gejala Klinis Pasien Covid-19 dengan Koinfeksi Tuberkulosis - Muhammad Gilang Wicaksana; Winni Maharani; Lisa Adhia Garina (UNISBA Press, 2023)
Abstract. Coronavirus disease 2019 (COVID-19) and tuberculosis (TB) are infectious diseases that can be transmitted by droplets. The clinical manifestations of COVID-19 disease can worsen if there are comorbidities, one of which is TB disease. Epidemiologically, COVID-19 and TB are two diseases with a very high incidence and are a global health problem. The study aims to analyze the impact of TB co-infection on the clinical symptoms of COVID-19 patients. This research uses the scoping review method using scientific articles published in three databases SciencDirect, SpringerLink, and Pubmed in 2019-2022. In the data search, 2,773 articles were obtained with the acquisition of 404 articles that met the inclusion criteria and 6 articles after PICOS analysis was carried out. The results showed that the dominant clinical symptoms that occurred at all ages were respiratory symptoms, fever, cough, chest pain, and dyspnea. In addition, there are additional clinical symptoms in pediatric patients in the form of nausea, diarrhea, headache, tachypnoea, and altered sensorium (impaired awareness, attention or difficulty focusing thoughts). Other results describe an increase in the release of cytokines (IFN-γ, TNF, IL-4, and IL-13) against both pathogens resulting in a